Peran Mediasi Motivasi Pada Stres Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Komisi Pemilihan Umum (KPU) Kota Probolinggo - Dedi Joko Hermawan; Tri Indah Landasari; Trivosa Aprilia Novadiani Haidiputri (CV. Ulil Albab Corp, 2024)
This study was conducted at the office of the General Election Commission (KPU) of Probolinggo City with the aim of determining the role of motivation mediation on work stress and workload on the performance of employees of the General Election Commission (KPU) of Probolinggo City. This type of research uses survey research and is associative causal. The population is 30 employees of the General Election Commission (KPU) of Probolinggo City and sampling using saturated sampling techniques of 30 respondents. The data collection methods used in this study are interviews, documentation and questionnaires distributed to respondents. The data analysis method from the results of the study is a quantitative method in the form of Convergent Validity test, Discriminant Validity and reliability test and conducting hypothesis testing using SmartPLS 3.0. The results of the study indicate that Work stress does not have a positive and significant effect on performance, Workload has a positive and significant effect on performance, Work stress has a positive and significant effect on motivation, workload has a positive and significant effect on motivation, motivation does not have a positive and significant effect on performance, work stress has a positive and significant effect on performance through motivation, and workload has a positive and significant effect on performance through motivation.